83.0k views
3 votes
Expand and simplify 2(5x+3)-2(2x-3)

User Dchar
by
6.2k points

2 Answers

0 votes

Answer:

hopes this helps.

Explanation:

Expand and simplify 2(5x+3)-2(2x-3)-example-1
User Fudge Fudge
by
5.8k points
5 votes

Hey there!


2(5x + 3) - 2(2x - 3)

DISTRIBUTE

= 2(5x) + 2(3) - 2(2x) - 2(-3)

= 10x + 6 - 4x - 6

COMBINE the LIKE TERMS

= (10x - 4x) + (6 + 6)

= 10x - 4x + 6 + 6

= 6x + 12


Therefore, your answer is: 6x + 12


Good luck on your assignment & enjoy your day!


~Amphitrite1040:)

User Bevan Collins
by
6.3k points